Мікроекономічні аспекти діагностики функціонування селянських господарств - Васильченко, Олена Олегівна; Васильченко, Елена Олеговна; Vasylchenko, Olena; Кунов, М. Р. (My University, 2020)
UK: В статті розглянуто особливості діагностики функціонування селянського господарства як специфічного соціально-економічного утворення. Обґрунтовано роль малих сімейних форм виробництва сільськогосподарської продукції як суб’єкту аграрних відносин та стабілізуючого фактору в системі сільських територій. Доведено необхідність розробки методичного інструментарію для ефективної діагностики розвитку селянських господарств в економічному та соціальному аспектах. В статті сформульовано основні цілі діагностики функціонування селянських господарств, а також розроблено алгоритм відповідних методичних заходів. Зазначається, що практичне застосування вказаних прийомів дозволить підвищити рівень ефективності виробничо-господарської діяльності представників даного сегменту аграрного виробництва. EN: Introduction. Under the current conditions of development of the national economy, the development of small forms of business, in particular those based on the family way of organizing functioning, is becoming increasingly important. The objective necessity of developing methodological approaches to the analysis of the character of the activities of the peasant farms at the appropriate stage of their functioning has made the research topic relevant. The purpose of this article is to analyze, develop and substantiate theoretical and methodological approaches to the diagnosis of economic activity of farms. Results. The results of the study proved the necessity of developing methodological tools for effective diagnostics of the development of farms in economic and social aspects. The main goals of diagnostics of functioning of peasant farms are formulated in the article, namely: identification of the state and nature of functioning, in particular the dynamics of development at a particular point in time; identification of the main factors that influenced the functioning of the peasant economy, assessment of the nature of the impact; forecasting of development trends, estimation of prospects of further functioning with possible adjustment. The article provides a list of specific indicators to achieve them, and also develops an algorithm for appropriate methodological measures. Conclusions. The peculiarities of diagnostics of functioning of the peasant economy as a specific socio-economic formation are investigated in the article. The necessity of optimizing methodological tools for effective diagnostics of the development of peasant farms is proved. It is noted that practical application of these techniques will increase the level of efficiency of production and economic activity of representatives of this segment of agricultural production, as well as stimulate the process of their transition to entrepreneurial principles of functioning.
Microeconomic aspects of diagnostics of functioning of villages agricultural holdings on the basis of cooperation
Keywords: селянське господарство; економічна діагностика; мікроекономічний аналіз; соціальний розвиток; peasant economy; economic diagnostics; microeconomic analysis; social development